The effect of Supply Chain Practices on Business Performance in PT.Putra Tunggal Perkasa - Devi Rahnjen Wijayadne; Timotius Fcw Sutrisno; Aria Ganna Henryanto; Bontor Dodi Pasaribu (Fakultas Bisnis, 2021)
Supply chain management has evolved into value chain management driven by consumer needs. Besides pursuing increased efficiency, it recognizes the importance of consumer needs and attempts to capture the intricacies of consumer value as a source of differentiation and competitiveness in the supply chain. The purpose of this study is to look at the effect of supply chain practices on PT. Mighty only son. This study uses a quantitative method with 30 respondents consisting of all non-driver staff. Based on the results of research on customer relationship variables, information quality, information technology can be concluded that these variables have an impact on business performance partially.